Introduction to Christian doctrines - Sivasubramanian, David Muthukumar (Bengaluru, India. Theological Book Trust (TBT)., 2024)
This book, Introduction to Christian Doctrines, is an exploration into the fundamentals of Christian beliefs that have shaped and continue to shape individuals and communities throughout the ages. This book is designed as an introductory guide for students embarking on this exploration-especially from the context of India-introducing them to diverse doctrinal expressions within the Christian tradition. The varied historical and sociocultural contexts that have shaped these doctrines and their impact on the life and practice of the Christian Church are clearly presented in this book.
Keywords: Christian Doctrines; Christian Doctrines.-- Introductions; Christian Doctrines.-- Indian Context; Fundamentals, Christian; Doctrinal Expressions.-- Christian Tradition